(untitled) (American Journal of Islam and Society, 2005)
The Islamic Social Services Association and Women in Islam have released a guide underlining a set of principles rooted in Islamic sources that outlines the rights of Muslim women to have full access to the mosque, and calling on Muslim leaders to privilege Islamic principles and values over cultural habits and traditions. The guide is entitled “Women-Friendly Mosques and Community Centers: Working Together to Reclaim Our Heritage.” The guide is a serious attempt to deal with an issue that requires immediate attention by Muslim communities: the place of women in the mosque and the community. I personally faced the issue for the first time two decades ago when a Muslim Student Association board member objected to the inclusion of women in an executive meeting. He based his position on Islamic tradition, but his argument was found lacking by everyone else on the board. The meeting went on without him, but with the two sisters. The point of view alluded to above has continued to be well-represented over the years within the Muslim community, particularly among immigrants who grew up in societies were women did not take an active role in social life and community development. The point of view that was hostile to the presence of women in the mosque gained more of a following in many Islamic centers throughout North America as the community grew more dependent on imams and scholars educated in universities that provide a narrow Islamic education. Hammered by Islamic opinions apparently rooted in Islamic sources, many mosques started to erect barriers and drop curtains between the men’s and women’s areas. Eventually, many mosques designated a separate and secluded area for Muslim women. The strict seclusion often mimicked arrangements adopted by mosques in Muslim countries and was tolerated by women who grew up in a condition of seclusion. American-born Muslim women, including women who grew up in immigrant families, find it increasingly difficult to accept the regime of seclusion in the mosque that cuts them off from education and decision making. Some have chosen to stay away and find alternative ways to acquire Islamic education and engage in social services. Others went back to understand Islamic sources and found out that there is no ground for the regime of seclusion. The “Women-Friendly Mosques” guide is the outcome of a quest by Muslim women who made the journey to examine the Islamic sources and to face head-on the arguments employed to perpetuate a regime that cuts Muslim women off from Islamic education and community service. The journey placed them in direct contact with the Islamic texts and put them in touch with Muslim scholars. The conclusion they came back with is both refreshing and relieving for every Muslim woman who was troubled with the sense of alienation that she had developed by visiting the center of Islamic life, whose Prophet, peace be with him, came to reaffirm the spiritual and moral equality of both men and women.